Design of Steel Lighting System Support Pole Structures - Engineers, American Society of Civil (Standards Ser., 2021)
Design of Steel Lighting System Support Pole Structures, ASCE/SEI 72-21, provides design parameters applicable to self-supporting structures, with base plates for installation on a concrete pier foundation, or as direct embedded, backfilled poles with the base section being either steel or concrete.